Leadership in Action: Pressure Cooking: Real Leaders Thrive When the Chips are Down - Jones, Graham (Center for Creative Leadership, 2009)
The role of the leader involves several principal tasks: creating a compelling vision, coming up with a strategy to achieve that vision, and communicating the vision and strategy to the organization's people. All of this puts the leader in a highly visible position, in which expectations can create enormous pressure. In tough economic times such as the world is experiencing now, this pressure is intensified. Leaders' success in such environments depends largely on the path they choose: to be safe leaders or real leaders.